Selected problems of diplomatic and consular immunities and functions in the case law of the European Court of Human Rights, from a Central European perspective - Czubik , Paweł (The ECHR at 70: The Central European Narrative, 2025)
The intensive development of human rights is increasingly affecting cross-border issues – including diplomatic and consular traffic. Although these areas are classic branches of international law, their development is increasingly influenced by the perception of the dignity of the human person and the proliferation of human rights norms. The following text examines the interplay of human rights and the issue of immunities to ensure the proper functioning of diplomatic missions and consular offices. This is a contentious matter. Attention is also given to consular functions, the task of which may also be to ensure the protection and dignity of the human person. A special place in this catalogue is occupied by the tasks of the foreign service in the field of diplomatic and consular protection. A special legal construction, whichcan be seen as being in line with due process standards, is the access to the consul of a person deprived of liberty. In this regard, international law has produced a rich jurisprudence. Finally, the text also devotes attention to the issue of consular functions regarding external voting – in this regard, an established standard of legal and human guarantees has not yet formed. Keywords: diplomatic and consular immunities, right of access to the consul, consular care, diplomatic protection, external voting.